La gran bonanza de las Antillas - Calvino, Italo; Bernárdez, Aurora; Calvino, Italo (Madrid : Siruela, 2012)
A collection of short stories covering the length of Italo Calvino's extraordinary writing career, from when he was a teenager to shortly before his death.
Online resource; title from ePub title page (Digitalia, viewed March 12, 2016)
Keywords: Electronic books